Antimicrobial Photodynamic Therapy Combined With Antibiotic in the Treatment of Rats With Third-Degree Burns - Zhao, Zhanjuan; Ma, Jinduo; Wang, Yiyi; Xu, Zehua; Zhao, Lu; Zhao, Jianxi; Hong, Ge; Liu, Tianjun (Frontiers in Microbiology, 2021)
Cationic porphyrin conjugate PPIX-MED has a potent photosensitive antibacterial effect on clinically-isolated bacteria including methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, and Pseudomonas aeruginosa. This study investigated (i) the PPIX-MED-mediated antimicrobial photodynamic effect on these three species in vitro; and (ii) the effect of antimicrobial photodynamic therapy (aPDT) combined with the use of an antibiotic on the healing in vivo of third-degree burns of rats with the wounds infected by these bacterial species. PPIX-MED exerted a potent inhibitory effect on the growth of the three bacterial species by producing reactive oxygen species when photoactivated. In vitro, PPIX-MED-mediated antimicrobial photodynamic therapy (PPIX-MED-aPDT) had high bacterial photoinactivation ability with a minimum inhibitory concentration of 16 µM PPIX-MED against each of the three types of bacteria, and minimum bactericidal concentrations of 31.25 µM against MRSA and E. coli, and 62.5 µM against P. aeruginosa. In rats with third-degree burns infected by a mixture of these bacteria, the bactericidal efficiency of PPIX-MED-aPDT combined with antibiotic treatment was higher than that of antibiotic- or aPDT-treatment alone. This was confirmed by analysis of viable bacterial counts in wound tissue and blood. Enzyme-linked immunosorbent assay revealed that aPDT combined with antibiotic treatment resulted in an obvious reduction in tumor necrosis factor-alpha and interleukin-6 levels compared with the no-treatment control group and the other treatment groups. Immunohistochemistry revealed that the expression of basic fibroblast growth factor and CD31, a marker of neovascularization, expressed in burn wound tissue was higher in the aPDT combined with antibiotic treatment group than in the other groups. PPIX-MED-aPDT has a promising bactericidal effect both in vitro and in vivo, and PPIX-MED-aPDT combined with antibiotic treatment enhanced the healing of infected third-degree burns in rats.